2007
DOI: 10.1002/app.25644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of both uncoated and coated calcium carbonate on fracture toughness of HDPE/CaCO3 nanocomposites

Abstract: The main goal of this research is to investigate the effect of nano-CaCO3 coated with different content of stearic acid on fracture toughness of HDPE/CaCO3 nanocomposite. For this purpose, HDPE/10 vol % CaCO3 nanocomposites were made using a twin-screw mixer-single-screw extruder. Nanocomposite standard samples were prepared via injection molding method. Three-point bending tests and microscopic evaluations were performed. The results of fracture toughness test showed that the addition of uncoated nano-CaCO3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 33 publications
3
68
0
1
Order By: Relevance
“…The melting point of neat HDPE is recorded at 127 C and the heat of fusion is 148.8 J/ g, while the melting points of HDPE with nanocomposites were also similar with the appeared differences being negligible (0.1-0.3 C). Sahebian et al 32 reported that nanosized calcium carbonate in HDPE/CaCO 3 nanocomposites present a significant effect on crystallinity, crystallization rates, melting point, and heat of melting of HDPE. Such a behavior was also observed using SiO 2 and MMT where the crystallization rates in both nanocomposites are higher, compared with neat HDPE, but the degree of crystallinity was reduced.…”
Section: Thermal Analysismentioning
confidence: 99%
“…The melting point of neat HDPE is recorded at 127 C and the heat of fusion is 148.8 J/ g, while the melting points of HDPE with nanocomposites were also similar with the appeared differences being negligible (0.1-0.3 C). Sahebian et al 32 reported that nanosized calcium carbonate in HDPE/CaCO 3 nanocomposites present a significant effect on crystallinity, crystallization rates, melting point, and heat of melting of HDPE. Such a behavior was also observed using SiO 2 and MMT where the crystallization rates in both nanocomposites are higher, compared with neat HDPE, but the degree of crystallinity was reduced.…”
Section: Thermal Analysismentioning
confidence: 99%
“…Compared to the neat HDPE-54 the fracture toughness of the composite samples decreased by about 50%. Similarly Zabardi et al 36 reported 37% reduction of fracture toughness of HDPE CaCO 3 nanocomposite at a similar CaCO 3 loading. In other words, addition of CaCO 3 led the composites samples toward brittle behavior.…”
Section: Fracture Toughnessmentioning
confidence: 91%
“…Uncoated CaCO 3 particles tend to aggregate and, as mentioned earlier, the agglomerated particles acted as stress concentrator points, hence reducing the fracture toughness and promote brittle fracture. [36][37][38][39] Moreover, from the morphological investigation of the fracture samples it was evident that there is no or little adhesion between the CaCO 3 particles and the HDPE polymer matrix. Since the filler/matrix interface is not strong enough thus deformation of the matrix interface is not the dominated energy absorption mechanism but rather debonding is suggested to be the controlling mechanism.…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…An improvement on thermal properties [4,[12][13][14][15], stiffness [5,[16][17][18][19][20], rheological properties [12,16,18,21] has been reported. While, several research studies have also been done in field of HDPE/CaCO 3 nanocomposites [3,4,18,[22][23][24].…”
Section: Introductionmentioning
confidence: 98%